2020
DOI: 10.1111/1365-2656.13306
|View full text |Cite
|
Sign up to set email alerts
|

How biological invasions affect animal behaviour: A global, cross‐taxonomic analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 84 publications
(83 reference statements)
0
25
0
Order By: Relevance
“…Laboratory experiments have shown that individual behaviour underlying group coordination can evolve in just a few generations [47,48]; however, such changes have yet to be documented in the field. Species invasions provide opportunities to observe evolutionary changes in behaviour [49,50]. In our study of an invasive population, we found less stable tandem runs than those previously observed in a native population of C. formosanus in Japan [19] (electronic supplementary material, figure S4).…”
Section: Discussionmentioning
confidence: 51%
“…Laboratory experiments have shown that individual behaviour underlying group coordination can evolve in just a few generations [47,48]; however, such changes have yet to be documented in the field. Species invasions provide opportunities to observe evolutionary changes in behaviour [49,50]. In our study of an invasive population, we found less stable tandem runs than those previously observed in a native population of C. formosanus in Japan [19] (electronic supplementary material, figure S4).…”
Section: Discussionmentioning
confidence: 51%
“…Laboratory experiments have shown that individual behavior underlying group coordination can evolve in just a few generations [39,40]; however, such changes have yet to be documented in the field. Species invasions provide opportunities to observe evolutionary changes in behavior [41,42]. In our study of an invasive population, we found less stable tandem runs than those previously observed in a native population of C. formosanus in Japan ([18], Supplemental text, Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Laboratory experiments have shown that individual behavior underlying group coordination can evolve in just a few generations [39,40]; however, such changes have yet to be documented in the field. Species invasions provide opportunities to observe evolutionary changes in behavior [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The prey naïveté hypothesis predicts that native prey often fail to recognize and/or avoid an introduced predator due to a lack of the coevolutionary history (Cox & Lima, 2006;Sih et al, 2010). Similarly, but in a different scenario where introduced species are prey for local predators, lack of native predator recognition by invasive prey can result in increased predation on the introduced species (e.g., Barrio et al, 2010;Carthey & Banks, 2018;Ruland & Jeschke, 2020). We observed that M. trilobatus frequently abandoned their webs after the predators' intrusion, and once outside their webs were easily subdued by Pachygnatha.…”
Section: Discussionmentioning
confidence: 99%